ANALISIS EFISIENSI TERMAL PADA KETEL UAP DI PABRIK GULA KEBONAGUNG MALANG - Heni Hendaryati (Jurnal Gamma, 2012)
ANALISIS EFISIENSI TERMAL PADA KETEL UAP DI PABRIK GULA KEBONAGUNG MALANGHeni HendaryatiStaf Pengajar Jurusan Teknik Mesin, Fakultas TeknikUniversitas Muhammadiyah MalangEmail : henihendaryati@yahoo.comABSTRACTAmid strong currents of globalization and the energy crisis such as rising fuel prices that hit the world’s sugar industry claimed to be more competitive to face increasingly fierce competition. Under these conditions, suppress the dissipation of energy and attention on energy conservation becomes an important thing to do. Source of energy for the process of sugar production in sugar mills Kebon Agung Malang generated from the boiler in the form of steam. The plant operates using 2 pieces of boiler, Boiler Yoshimine H-2700 with a capacity of 80 tons / hour and Boiler Yoshimine H-3500 with a capacity of 100 tons / hour. This study aims to determine the efficiency of boilers used and assess energy conservation in the boiler. During this study, the boiler is in operation with fuel bagasse (bagasse). Data is collected by recording directly from the control panel. Data is taken every hour for 24 hours a day, the study was conducted for 30 days. Research shows the average thermal efficiency by the heat balance method for the Boiler Yoshimine H-2700 was 74.8% and Boiler Yoshimine H-3500 was 73.9%. Sankey Diagrams Based on the amount of heat entering the steam boiler for the second kettle is 1713.194 kcal / kg. Heat lost to Boiler Yoshimine H-2700 is 425.915 kcal / kg, so the heat is used is 1287.279 kcal / kg. While the heat lost to Boiler Yoshimine H-3500 is 445.653 kcal / kg, so the heat is used is 1267.541 kcal / kg.Key note : Boiler, heat balance, efficiency